Praktik Politik Oligarki dan Mobilisasi Sumber Daya Kekuasaan Di Pilkades Desa Sitimerto Pada Tahun 2016 - Hidayat, Endik (Sospol : Jurnal Sosial Politik, 2018)
The emergence of a debate about the village head elections, is it a form of democracy or not democracy? Because it is controlled by a handful of oligarchs, it has long occurred among village experts. Therefore, this article aims to find out the development of the democratic model and the source of oligarchic power in Sitimerto village, Kediri regency in the Pilkades 2016. This article uses a qualitative approach and takes a case study on the selection of Sitimerto village heads, Pagu District, Kediri District, East Java Province. The case was interesting because the Sitimerto Pilkades allegedly represented a village with Javanese cultural characters and the oligarchs were quite strong. The results of the study prove that material resources are still dominant in the political dynamics of Sitimerto village. Money politics is a material resource that functions to influence village voters with diverse meanings. However, oligarchs must also become as elites to be able to exploit non-material resources to better guarantee victory in the election of the Sitimerto village head. In this study, non-material resources are identical with Javanese sources of power which are spiritual powers or called kesakten.